LAS ANOTACIONES DE L.I. ESCOPA A LA OBRA DE PERSIO - del Amo Lozano, Milagros (Myrtia, 1997)
In this essay different comentaries by L.I. Scoppa are analyzed and valorated. They are notes that this 16th. century humanist includes in his work 'In varios authores Collectanea' and they explain some quotations by Persius: pr. 13; pr. 14; I 76; II 14 and IV 22.